2017
DOI: 10.1007/s00167-017-4645-0
|View full text |Cite
|
Sign up to set email alerts
|

The Shoulder Instability-Return to Sport after Injury (SIRSI): a valid and reproducible scale to quantify psychological readiness to return to sport after traumatic shoulder instability

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 27 publications
(31 reference statements)
2
96
5
1
Order By: Relevance
“…Psychological readiness is an important element for optimal RTP. Emotions including fear of re-injury and cognitive factors including self-efficacy and motivation influence treatment and outcome after athletic injury [69].…”
Section: The Decision-based Return To Play Modelmentioning
confidence: 99%
“…Psychological readiness is an important element for optimal RTP. Emotions including fear of re-injury and cognitive factors including self-efficacy and motivation influence treatment and outcome after athletic injury [69].…”
Section: The Decision-based Return To Play Modelmentioning
confidence: 99%
“…Furthermore, follow-up included documentation of the Rowe score, the Shoulder Instability-Return to Sport after injury (SIRSI) score, the Visual Analogue Scale (VAS) score, and the Subjective Shoulder Value (SSV) score, recurrence of dislocations or subluxations, revision surgeries, and complications. [7][8][9] All patients were assessed by a single investigator, who was not involved in the surgical procedures (EH). Internal review board approval was obtained prior to the start of the investigation.…”
Section: Data Collectionmentioning
confidence: 99%
“…The Anterior Cruciate Ligament-Return to Sport Index has been shown to be a useful prognostic tool for RTS after an ACL injury. 10 Gerometta et al 41 showed that a similar scale, the Shoulder Instability Return to Sport after Injury (SIRSI), is a valid and reliable scale to help identify athletes’ psychological readiness to RTS after traumatic anterior shoulder dislocation. Studies incorporating use of the SIRSI scale, alongside other psychological factors shown to positively correlate with RTS in the lower limb 8,96 (motivation, self-confidence, and slight fear), are warranted in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“… ∥ ∥References 11, 12, 14, 16, 18, 20, 24, 28, 30, 32, 34, 36, 41, 47 - 49, 52, 58, 59, 70, 71 - 75, 79, 83, 84, 86, 90, 94, 96. …”
mentioning
confidence: 99%